Konsep Pendidikan Islam dalam Pembentukan Kehidupan Manusia yang Seimbang - Istiqomah Nurul Azizah; Nadzani Pramudya Ibni; Zahwa Putri Naila; Soffia Soffia; Wismanto Wismanto (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Islamic education views life as having two basic components: the material, or worldly, life and the spiritual, or moral, life that leads to a wealthy and joyful life in the hereafter. As a result, the Islamic educational system polarizes life in order to seek satisfaction both here on Earth and in the hereafter. Humans are impacted by a multitude of aspects in their lives, including educational background, morality, and ubudiyah, when it comes to reaching their goals in life. Then, Islamic education is required to help people develop both physically and spiritually in order to assist the balanced attainment of human life's goals in this world and the next. Since humans must strive to seek Allah SWT's gift in order to satisfy all of their wants, human physical growth is focused on attaining the welfare of human existence in this world. Naturally, individuals require a robust and healthy body in order to attempt. The goal of human spiritual growth is to provide welfare for people, both in this life and in the next.